Peranan BPR Syariah Alwashliyah Dalam Meningkatkan Bisnis UMKM Melalui Pembiayaan Murabahah - Simanjuntak, Wiwin Khairany; Dalimunte, Ahmad Amin (LPPM Universitas Labuhanbatu, 2022)
This study intends to decide the job of BPR Syariah in further developing MSMEs in Medan City. This kind of exploration is engaging subjective. The subjects in this study were the gatherings who were utilized as witnesses in a review. There are two witnesses who go about as sources in this review, to be specific the functional head of PT. BPRS Al-Washliyah upwards of 1 individual and staff of the Murabahah Financing Division of PT. BPRS Al-Washliyah upwards of 2 individuals. The procedure for gathering information was finished by utilizing a meeting test as questions connected with the exploration. The outcomes showed that the extent of the biggest number of clients was in June 2018 as numerous as 12%. While the most minimal level of the quantity of clients was in February 2018 which was just 6%, the all out income from murabahah funding items got from 2014 to 2018 expanded and was straightforwardly relative to the expansion in the quantity of clients from 2014 to 2018. This makes the job of BPRS progressively significant in the MSME area. BPRS Al-Washliyah obliges local area organizations beginning at the miniature level. With every one of the upsides of the standards did, the Medan City MSME entertainers proceed to create and develop quickly. Simultaneously adding the presence of BPRS Al-Washliyah in fostering the local area's economy.